METHODOLOGY FOR USING CASE ASSIGNMENTS IN TEACHING THE TOPIC” IRON AND ITS COMPOUNDS - Mamadaliyeva Nodira Isakovna (Web of Journals Publishing, 2023)
This article talks about the Case study method and its use in teaching the topic "Iron and its compounds".
Keywords: Case stage, method, educational technology, iron,